Early conch morphology of a gigantic Cretaceous ammonoid, Pachydesmoceras denisonianum (Desmoceratidae) - Ryoji Wani (PeerJ)
Gigantic ammonoids, with conch diameters exceeding 1 m, remain one of the most enigmatic groups of extinct organisms. Their paleoecology has been the subject of ongoing debate, with some uncertainties arising from preservation biases, especially of an early conch. This study focuses on an exceptionally preserved early conch of the giant Cretaceous ammonoid Pachydesmoceras denisonianum from southern India. Conch morphology and the ontogenetic trajectories of constrictions and septal spacings were examined. The results indicate that constrictions were frequently present in the early conch; based on the shell layers observed in the cross-section, these constrictions likely resulted from periods of halted or slowed growth. The common occurrence of constrictions during early ontogeny suggests that Pachydesmoceras lifespan may have been longer than previously assumed. Additionally, the ontogenetic patterns of septal spacing might not reflect these growth halts or slowdowns in the examined species.